Dinamika spirit of place pada GPIB Immanuel dan Pancaran Kasih di Depok - Damayanti, Riajeng Sinta; Salura, Purnama (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
This study discusses the spirit of place which is also known as the “genius loci” of two GPIB church buildings in Depok, Indonesia. It is important to note that the physical and spatial order of a structure theoretically has an expression usually interpreted according to the character and identity created by the observer or user. This means it is possible for buildings with the same function, liturgy, and space requirements but different physical arrangements to have the same spirit of place. The focus of this study is on the church of GPIB Immanuel and GPIB Pancaran Kasih in Depok and it was conducted qualitatively and descriptively through anatomical and phenomenological methods. The operational stage involves the emic steps which include field observations and structured or unstructured interviews for managers and informants doubling as the users of the buildings as well as ethical steps which are focused on the study of architectural theories. The results showed that the physical architectural order of the two churches creates a dynamic character and identity as well as a spirit of place even though they come from the same synod, order, and have the same liturgy and procession. This was discovered to be due to their similarities and differences.